Analysis Of Bank Performance Before And After Covid 19 In Banking Companies Listed On Idx - Romli; Zaputra, Ali Rahman Reza (Publisher Cv. Inara, 2022)
This study aims to analyze the banking performance before and after covid 19 in banking companies listed on the IDX. In this study, the banking performance indicators analyzed are the CAR (Capital Adequacy Ratio), BOPO (Operating Expenses to Operating Income), NIM (Net Interest Margin), LDR (Loan to Deposit Ratio), and ROA (Return On Assets). The sample used is banking companies listed on the Indonesia Stock Exchange (IDX) in 2019 and 2020 with the total of 43 banks. This study an event to examine the differences or changes in banking financial performance, before covid 19 and after covid 19. The data analysis technique used is the average difference test using SPSS program. Based on the test results, it was found that the COVID-19 pandemic caused the BOPO, NIM, LDR and ROA ratios to decrease or worsen, while the CAR ratio increased.